FLOORS, FLOOR COVERING AND WALL FINISHING PRACTICES IN BUILDING CONSTRUCTION IN RURAL AREAS IN ZAMFARA STATE, NIGERIA - Kaura, Tijjani Halima; Emmanuel, Raymond; Dauda, Ibrahim (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
This study determined floors, floor covering and wall finishing practices adopted by craftsmen in building construction in rural areas of Zamfara State, Nigeria. The descriptive survey research design was used for the study on a sample size of 322 master craftsmen comprising of 253 with educational qualification and 69 without educational qualification gotten with the aid of National Statistical Service Sample Size Calculator. An 11 item validated questionnaire with a Cronbach Alpha reliability of 0.84 was used for collecting data for the study. Mean and the standard deviation was used to answer the research questions while t-test was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that: the building construction floors, floor covering and wall finishing practices are not highly adopted by building master craftsmen in rural areas. There was no significant difference between the mean responses of the respondents on the building construction floors, floor covering and wall finishing practices adopted by building master craftsmen in rural areas. This implies that the incessant cases of building failures in rural areas could be attributed to the negligence towards the adoption of standard building construction floors, floor covering and wall finishing practices in rural areas. It was recommended that there is urgent need for all categories of building craftsmen to highly adopt the building construction floors, floor covering and wall finishing practices stipulated by the standard building code to enhance the performance strength of buildings in rural areas as well as improve their building construction floors, floor covering and wall finishing practices of craftsmen in rural areas of Zamfara State, Nigeria.